2006
DOI: 10.1097/01.inf.0000243158.25713.29
|View full text |Cite
|
Sign up to set email alerts
|

Community-Associated Methicillin-Resistant Staphylococcus Aureus Necrotizing Fasciitis in a Neonate

Abstract: Neonatal necrotizing fasciitis is rare and is predominantly associated with methicillin-susceptible Staphylococcus aureus (MSSA). Necrotizing fasciitis associated with community-associated methicillin-resistant S aureus (CA-MRSA) has only recently been reported in the literature, primarily among adults. We present a case of a previously healthy neonate with necrotizing fasciitis of the back caused by CA-MRSA, pulsed-field type USA-300. We describe a 5-day-old infant with necrotizing fasciitis of the back cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The majority of the isolates were USA300 MRSA strains but were resistant to clindamycin and ciprofloxacin (803). Cases of severe, fatal neonatal MRSA pneumonia caused by USA300 have also been reported among neonates (590,1019), as has necrotizing fasciitis (224).…”
Section: Neonatal Mrsa Infections and Maternal Colonization And Infecmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the isolates were USA300 MRSA strains but were resistant to clindamycin and ciprofloxacin (803). Cases of severe, fatal neonatal MRSA pneumonia caused by USA300 have also been reported among neonates (590,1019), as has necrotizing fasciitis (224).…”
Section: Neonatal Mrsa Infections and Maternal Colonization And Infecmentioning
confidence: 99%
“…Infectious foci should be drained, and necrotic tissue should be debrided when feasible (7,87,159,224,379,523,525,609,1021).…”
Section: Severe Infectionsmentioning
confidence: 99%
“…Recent reports (mostly case reports and case series) of necrotizing SSTIs caused by CA-MRSA have revealed that this type of necrotizing SSTI presents more subacutely and is a more benign syndrome than necrotizing infections caused by other etiologies [13,[42][43][44]. In a retrospective study of 14 patients with necrotizing SSTIs, 57% of patients had a preoperative diagnosis of abscess, and necrotizing infection was not suspected [13].…”
Section: Clinical Presentationmentioning
confidence: 95%
“…The inclusion of antimicrobials effective against MRSA in suspected staphylococcal infection is recommended for high-risk patients (eg frequent hospital attendees or residents of long-term care facilities), and for neonates and children as well [18,20]. With a history of "spider bite" or recurrent skin sepsis, CA-MRSA should be suspected and the addition of vancomycin, daptomycin, or linezolid is recommended.…”
Section: Antimicrobialsmentioning
confidence: 98%
“…Methicillin-resistant Staphylococcus aureus (MRSA) NF, [8][9][10][11][12] including Fournier's gangrene [15], is now increasingly reported, especially with the spread of community-associated MRSA (CA-MRSA) [16][17][18][19][20][21]. CA-MRSA NF can cause purpura fulminans easily confused with meningococcal septicaemia clinically [21].…”
Section: Type 2 Nfmentioning
confidence: 99%